Improvement in cassava yield per area by fertilizer application - Omondi, J.O.; Yermiyahu, U. (IntechOpen, 2021)
Cassava is a source of carbohydrates to more than 200 million people in Sub-Saharan Africa, even though its production is 6–8 t ha−1, which is below the highest world production of 36.4 t ha−1 in India. To address this yield gap and increase cassava’s availability, affordability, and adequacy, intensive but sustainable production is important. Additionally, being an emerging raw material in the animal feeds, pharmaceutical, beer industries etc., only increases its demand, however the current production levels cannot effectively sustain this. Therefore, this paper reviews: improvement in cassava yields per area under fertigation and banding of fertilizers, a common practice among many farmers; the advantage of fertilizer application on starch of the storage roots, which is the fundamental ingredient in most industries using cassava as a raw material; and the climate smart technologies for intensive sustainable cassava production. In the end, this review enhances knowledge about fertilizer application to cassava, both banding and fertigation, and expounds on effective intensive sustainable climate-smart production strategies.